Current Status of Adverse Drug Reactions Monitoring Centres under Pharmacovigilance Programme of India - Kalaiselvan, V; Thota, Prasad; Singh, Abishank (Indian Journal of Pharmacy Practice)
There are one hundred and fifty Adverse Drug Reactions Monitoring Centres (AMCs) across the country are functioning and reporting’s Adverse Drug Reactions to National Coordination centre (NCC), Pharmacovigilance Programme of India (PvPI) at Indian Pharmacopoeia Commission (IPC), Ghaziabad. The AMCs are established to collate data on Pharmacovigilance and forward to NCC via online software (VigiFlow). The present AMCs are Medical Council of India (MCI) approved teaching hospitals and corporate hospitals. NCC is working with AMCs to coordinate with Pharmacy institutions to enhance ADRs reporting.
Keywords: Adverse Drug Reactions Monitoring Centres; Pharmacovigilance Programme of India; Vigi Flow. CDSCO. Indian Pharmacopoeia Commission